Thermally-induced flexible composite phase change material coupled multi-cross-linked network aerogel material and thermal protection application

By using the coupling technology of biomass-based composite aerogel with multiple cross-linking networks in the thermal protection materials of lithium batteries, the poor mechanical performance of existing thermal protection materials in lithium batteries is solved. and the problem of high flammability, achieving more effective heat management and reducing the risk of fire and explosion, suitable for a variety of thermal protection applications.

CN119144298AActive Publication Date: 2024-12-17DALIAN UNIV OF TECH

Patent Information

Application Number
CN202411344344.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-17
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

Existing thermal protection materials have problems such as poor mechanical properties, high flammability, and insufficient heat transfer in the thermal runaway scenarios of lithium batteries, resulting in insufficient thermal protection effect and it is difficult to effectively delay the risk of heat diffusion and fire explosion.

Method used

Biomass-based composite aerogel using multiple crosslinking networks is coupled with thermogenic flexible composite phase change material, crosslinking gelatin with sodium alginate through glutaraldehyde and boric acid, and forming an aerogel with inorganic solid-liquid phase change material and The thermally conductive enhancer combines to form a stable crosslinking network structure, which is coupled together with adhesives to form a material system that can continuously absorb and remove heat.

Benefits of technology

It significantly improves the insulation duration and thermal protection performance of the material, delays heat diffusion, enhances flame retardant performance, and effectively reduces the risk of fire and explosion caused by thermal runaway from lithium batteries. It is suitable for thermal in buildings, electronic devices and lithium batteries. Protection field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144298A_ABST
    Figure CN119144298A_ABST
Patent Text Reader

Abstract

The invention discloses a thermally-induced flexible composite phase change material coupled multi-crosslinking network aerogel material and thermal protection application, and belongs to the technical field of new materials. The coupling material is composed of multiple cross-linked network aerogel, a thermally-induced flexible composite phase change material and a binder. Wherein the thermally-induced flexible composite material is a hydrated inorganic salt phase-change material, the binder is a flame-retardant inorganic binder, and the multi-crosslinked network aerogel is a sodium alginate / gelatin composite material and is crosslinked through a double-crosslinking agent to form a stable multi-network structure for improving the flame retardance and mechanical strength of the aerogel. The prepared coupling material has high flame retardance and good heat insulation performance, and is very suitable for large-scale application in the field of thermal protection in buildings, batteries and electronic devices in the future.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a thermo-flexible composite phase change material coupled with a multi-crosslinked network aerogel coupling material and a thermal protection application, and belongs to the technical field of new materials. Background Art

[0002] In recent years, the application of thermal runaway protection materials in buildings, batteries and electronic devices has been gaining increasing attention due to their key role in improving safety and functional reliability. For example, in the field of construction, the fire risks faced by modern high-rise buildings and confined spaces have made thermal runaway protection materials an important part of the design. These materials can not only significantly improve the fire resistance of buildings, but also effectively insulate high temperatures, slow the spread of fire, and protect building structures from damage by extreme heat. In electronic devices, thermal runaway has become a major challenge as the power density of equipment increases. Electronic devices may generate too much heat when running at high loads, causing the system to overheat and possibly cause failures. Thermal runaway protection materials can play an important role in the design of these devices, giving people time to deal with reactions through effective thermal management. Similarly, in the field of battery technology, especially in the application of lithium-ion batteries, thermal runaway has become a serious safety hazard. In recent years, fires and explosions caused by thermal runaway of lithium batteries have occurred frequently. This is because when a single lithium battery is overcharged, short-circuited or otherwise abused, a large amount of heat will be generated in a short period of time. When the battery temperature reaches 100–130 °C, the diaphragm begins to melt, causing an internal short circuit, which in turn triggers thermal runaway, bringing a high risk of fire or even explosion. What's more serious is that in order to meet high energy requirements, multiple single cells are usually assembled into a battery module. Once a single cell in the module has thermal runaway, the heat may spread to the adjacent cells through heat transfer, causing the entire battery module to have thermal runaway. Compared with single cells, the heat and hazards released by the thermal runaway of the entire battery module are more serious, which may cause catastrophic fires or explosions. Therefore, it is very important to develop suitable thermal protection materials to improve the thermal safety of the entire battery module. At present, thermal protection materials used for thermal runaway of lithium batteries are mainly divided into two categories: one is thermal insulation materials, such as aerogels; the other is heat absorption materials, such as phase change materials. These two types of materials delay the accumulation and transfer of heat by means of insulation or heat absorption, buying more time for the cooling and safe handling of lithium batteries.

[0003] In recent years, aerogel materials, as representatives of thermal insulation materials, are considered to be the most suitable for the field of thermal insulation because of their low thermal conductivity, ultra-light weight and low volume density. For example, inorganic aerogels (such as SiO2) have extremely low thermal conductivity, but are difficult to form, which limits their wide application; while organic aerogels (such as polyurethane, polyimide, etc.) have good forming properties, but the synthesis process is complicated, involving toxic solvents and raw materials, which may cause environmental pollution. In contrast, aerogels based on natural biomass have attracted widespread attention from researchers because of their wide sources, low prices and environmental protection. However, biomass aerogels also have defects. For example, sodium alginate aerogels have poor mechanical properties; and gelatin aerogels derived from collagen are flammable and have poor smoke suppression. Therefore, the development of high-performance biomass-based composite aerogels with good mechanical properties and flame retardant properties is of great significance for their application in the field of thermal protection of lithium batteries, but this challenge remains huge.

[0004] As a representative of heat-absorbing materials, phase change materials are considered suitable for the field of thermal protection because of their high latent heat density, small volume change, and ability to absorb a large amount of heat during the phase change process. However, most of the phase change materials currently used for thermal management of lithium batteries are organic solid-liquid phase change materials. Although they are chemically stable, their flammability is a fatal flaw. In the event of thermal runaway of lithium batteries, flammable organic phase change materials may increase the thermal hazards of the entire battery system and increase the risk of combustion and explosion. In contrast, inorganic solid-liquid phase change materials are not only completely non-flammable, cheaper, but also have higher latent heat values. However, inorganic solid-liquid phase change materials have problems with leakage and crystal rigidity. How to overcome these problems and give them flexibility is of great significance for their application in the field of thermal protection.

[0005] In addition to the problems with their own materials, the above two categories of thermal protection materials also have some problems in their application in the field of thermal protection. For example, as the energy density of lithium batteries becomes higher and higher, when aerogels become thermally saturated, they can no longer block all excess heat; and this is even more true for phase change endothermic materials. Once their latent heat and thermochemical heat storage value are exhausted, the phase change material will no longer be able to maintain a constant temperature, and thus will not be able to block the transfer and spread of excess heat. Therefore, how to delay the occurrence of thermal saturation, delay the diffusion of heat to the greatest extent, and provide more time for the safe handling of batteries is of great significance for their application in the field of thermal protection. Summary of the invention

[0006] In response to the above problems, this paper uses gelatin combined with sodium alginate as the main body of the aerogel, and glutaraldehyde and boric acid as double cross-linking agents to prepare a biomass-based composite aerogel with a multiple cross-linking network; at the same time, an inorganic solid-liquid phase change material (such as SAT) is used as the phase change main body, and a thermoplastic polyester elastomer (such as TPEE) and a thermal conductivity enhancer (such as EG) are used as packaging materials to successfully prepare a thermo-flexible composite phase change material. In addition, the present invention proposes for the first time to couple the Ge / SA composite aerogel with a thermo-flexible composite phase change material (such as SAT / TPPE / EG) through a binder, so that the SAT / TPPE / EG composite phase change material can continuously "charge and store energy" for the Ge / SA aerogel, absorb and remove heat for it in a timely manner, thereby delaying the occurrence of thermal saturation, maximizing the insulation time of the composite material, and delaying heat diffusion, so that it can be well applied in the field of thermal protection of lithium batteries.

[0007] The coupling material is a multi-crosslinked network aerogel coupled thermo-flexible composite phase change material, which is composed of 0.5-1.5wt% of multi-crosslinked network aerogel, 96.5-97.5wt% of thermo-flexible composite phase change material and 1-3wt% of binder by mass percentage. The thermo-flexible composite material is a hydrated inorganic salt phase change material, the binder is a flame retardant inorganic binder, and the multi-crosslinked network aerogel is a sodium alginate / gelatin composite material, which is cross-linked by a double crosslinking agent to form a stable multi-network structure for increasing the flame retardant performance and mechanical strength of the aerogel.

[0008] Preferably, the thermo-flexible composite phase change material is composed of 72-82wt% of inorganic solid-liquid phase change material, 1.0-2.0wt% of thermal conductivity enhancer and 17-27wt% of polymer support material by mass percentage. The phase change material can maintain a uniform and stable shape to meet the thermal protection requirements.

[0009] Preferably, the inorganic solid-liquid phase change material is one to three of sodium acetate trihydrate, calcium sulfate dihydrate, potassium aluminum sulfate dodecahydrate, ammonium aluminum sulfate dodecahydrate, magnesium chloride hexahydrate, magnesium sulfate heptahydrate, calcium nitrate tetrahydrate, zinc chloride hexahydrate and sodium thiosulfate pentahydrate.

[0010] Preferably, the thermal conductivity enhancer is one to three of expanded graphite, carbon nanotubes, carboxylated carbon nanotubes, graphene, graphene oxide, titanium dioxide, aluminum oxide, zinc oxide, sodium chloride, nanosilver, nanocopper, and nanogold.

[0011] Preferably, the main polymer support material is one to three of styrene-isoprene-styrene block copolymer (SIS), styrene-butadiene-styrene block copolymer (SBS), styrene-ethylene-butylene-styrene block copolymer (SEBS), hydrogenated styrene-isoprene-styrene block copolymer (SEPS), and thermoplastic polyester elastomer (TPEE).

[0012] More preferably, the multi-crosslinked network aerogel comprises 50% to 70wt% gelatin, 29 to 49wt% sodium alginate, 0.5 to 3wt% crosslinking agent boric acid, and 0.5 to 3wt% crosslinking agent glutaraldehyde by mass percentage. The multi-crosslinked network aerogel has high thermal insulation and flame retardant properties, meeting the thermal protection requirements.

[0013] Another object of the present invention is to provide a method for preparing the above-mentioned multi-crosslinked network aerogel coupled thermally induced flexible composite phase change material.

[0014] The method comprises the following steps:

[0015] (1) mixing gelatin and sodium alginate, stirring and heating to dissolve them in an acetic acid solution; then, adding boric acid, stirring and then adding a glutaraldehyde solution;

[0016] After being stirred together, the obtained solution is placed in a mold, then frozen, and finally freeze-dried in a freeze dryer to obtain Ge / SA aerogel;

[0017] (2) Dissolve the polymer support material in dichloromethane solution until it is uniformly dissolved.

[0018] Secondly, the inorganic solid-liquid phase change material is heated to a liquid state, and a thermal conductivity enhancer is added thereto for adsorption, and then the material is crushed by a ball mill, and then added to a polymer support material solution for mixing and adsorption; the solvent is removed to obtain a thermally induced flexible composite phase change material;

[0019] (3) The binder is coated on the surface of the thermoflexible composite phase change material, and then the Ge / SA aerogel is placed on the surface and cured at room temperature to obtain a multi-cross-linked network aerogel coupled thermoflexible composite phase change material.

[0020] Preferably, the specific steps are as follows:

[0021] (1) Mix 1.0 g of gelatin (Ge) and 0.4 g of sodium alginate (SA), stir and heat to dissolve in acetic acid solution. Then, add 0.01 g of boric acid, stir for 2 h, and then add 167 μL of glutaraldehyde solution. After stirring together for 0.5 h, put the resulting solution into a mold, then freeze it in a refrigerator at -20°C for 12 h, and finally freeze-dry it in a freeze dryer for 24 h to obtain Ge / SA aerogel;

[0022] (2) At 50°C, thermoplastic polyester elastomer (TPEE) was dissolved in the solvent. After half an hour, TPEE was evenly dissolved. Secondly, SAT was heated to a liquid state at 50°C, and expanded graphite (EG) was added thereto for adsorption. The adsorbed powder was then crushed using a ball mill and placed into the TPEE solution for mixing. The mixture was then adsorbed in a vacuum drying oven at 50°C for two hours. Subsequently, the mixture was placed in the air to cause the solvent dichloromethane to volatilize. Finally, the sample was placed in a vacuum drying oven for 24 hours to remove the residual dichloromethane solvent, thereby obtaining a thermo-flexible composite phase change material.

[0023] (3) The binder is coated on the surface of the thermo-flexible composite phase change material, and then the Ge / SA aerogel is placed on the surface and then cured at room temperature for 48 h.

[0024] In the above technical scheme, the solvent is preferably 1 to 3 of tetrahydrofuran, dioxane, petroleum ether, acetone, butanone, chloroform, dichloromethane, carbon tetrachloride, carbon disulfide, DMF, DMSO, benzene, toluene, xylene, nitrobenzene, chlorobenzene, cyclohexane or n-hexane.

[0025] Another object of the present invention is the application of the multi-crosslinked network aerogel coupled with thermally flexible composite phase change material, which is used in the field of thermal protection in buildings, batteries and electronic devices.

[0026] The beneficial effects of the present invention are:

[0027] The present invention is based on the property that the chemical cross-linking network formed by gelatin and glutaraldehyde can provide mechanical strength for the composite aerogel; the hydrogen bond cross-linking network formed by sodium alginate and boric acid is used to improve the flame retardant properties of the composite aerogel; thus, a biomass composite aerogel with good mechanical properties and flame retardancy is constructed. At the same time, through the elastic behavior support performance of the polymer support material (TPEE, etc.), the porous adsorption characteristics of the thermal conductivity enhancer EG, and the double encapsulation strategy, a composite phase change material with thermal flexibility is constructed. Finally, the two are coupled together by a binder to maximize the thermal protection performance of the coupling material.

[0028] Sodium acetate trihydrate has two main heat storage stages: latent heat storage (58°C) and thermochemical heat storage (106-140°C). These two temperature stages can not only provide early warning for thermal runaway, but also inhibit heat propagation when thermal runaway occurs.

[0029] The thermo-flexible composite phase change material in the present invention can continuously "charge and store energy" for Ge / SA aerogel like a power bank, and timely absorb and remove heat for the thermo-flexible composite phase change material, thereby delaying the occurrence of thermal saturation, maximizing the insulation time of the composite material, and delaying heat diffusion, so that it can be well applied to thermal protection fields such as construction, electronic devices, and lithium batteries. Compared with uncoupled thermo-flexible composite phase change materials / aerogel materials, their thermal protection effect is greatly improved.

[0030] In order to evaluate the thermal protection effect of the prepared coupling material, we chose to conduct an actual simulated thermal insulation test on it. A ceramic heating plate (35*21*5 mm) was used to simulate a high temperature environment to evaluate the thermal insulation performance of the composite material. First, the material to be evaluated was placed on the ceramic heating plate, and the two were fixed with a mold, and then the thermocouples were placed on both sides of the sample to be tested. Subsequently, a DC regulated power supply (IT6722A, China Itech Electronics Co., Ltd.) was used to power and heat the ceramic heating plate, and a temperature recorder (MIK-R5000C, Hangzhou Meikong Automation Technology Co., Ltd., China) was used to record the temperature difference on both sides of the sample to evaluate the thermal insulation performance of the sample.

[0031] The present invention tests the thermal insulation performance of the composite material Ge / SA-STE formed by the Ge / SA composite aerogel and SAT / TPPE / EG respectively. It can be seen that the thermal insulation performance of the Ge / SA composite aerogel in the combination mode of being on the top close to the heat source is better, and the temperature can be controlled below 90°C. In addition, the present invention also measures the thermal insulation performance of STE and Ge / SA aerogel at the same thickness. It can be found that the final upper temperature of STE is about 182°C, while the final upper temperature of GE / SA is 111°C, which are not as good as the thermal insulation performance of the coupling of the two at the same thickness. This proves the superiority of the coupling material of the present invention, which has good thermal protection ability and has great practical application value.

[0032] The research results show that the prepared Ge / SA-STE coupling material exhibits very good thermal insulation performance. Even at a high temperature of 200 °C, after 60 minutes, the temperature at the top is still 88 °C. In addition, the coupling material also has very good flame retardant properties, which is very suitable for large-scale application in the field of thermal protection of lithium batteries and delaying the occurrence of thermal runaway of lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 a is the infrared spectra of Ge aerogel, SA aerogel and Ge / SA aerogel in Example 1; b is the pore size distribution corresponding to the nitrogen adsorption-desorption curves of Ge, SA and Ge / SA composite aerogel in Example 1; c is the pore size distribution corresponding to the cumulative mercury injection of Ge, SA and Ge / SA composite aerogel in Example 1.

[0034] Figure 2 a is the compressive strength of Ge aerogel, SA aerogel and Ge / SA aerogel in Example 1; b is the limiting oxygen index of Ge, SA and Ge / SA composite aerogel in Example 1; c is the thermal insulation effect diagram of Ge, SA and Ge / SA composite aerogel in Example 1.

[0035] Figure 3 Figure a is an image showing the changes in the morphology of SAT with heating time in implementation case 1; and an image showing the changes in the morphology of STE with heating time.

[0036] Figure 4 (a) is a photograph of the bending of STE at different temperatures in implementation case 1.

[0037] Figure 5 a is the DSC spectra of SAT, SAT / TPEE and SAT / TPEE / EG in implementation case 1; b is the limiting oxygen index of SAT / TPEE and SAT / TPEE / EG; c is the thermal insulation performance of the heating plate and SAT / TPEE / EG at different thicknesses.

[0038] Figure 6 a is the thermal insulation performance of the heating plate and Ge / SA-STE in different bonding methods in Example 1; b is the thermal insulation performance of the heating plate, Ge / SA and STE in Example 1. DETAILED DESCRIPTION

[0039] The following non-limiting embodiments may enable a person skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.

[0040] The test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0041] One of the specific implementations:

[0042] The preparation method and application of a multi-crosslinked network aerogel coupled thermo-flexible composite phase change material, wherein the coupling material of the two is composed of the following components by mass percentage:

[0043] Multi-crosslinked network aerogel: 0.5~1.5wt%;

[0044] Thermally induced flexible composite phase change material: 96.5~97.5wt%;

[0045] Binder: 1~3wt% composition.

[0046] The thermo-flexible composite material is composed of the following components by mass percentage:

[0047] Inorganic solid-liquid phase change material: 72~82wt%;

[0048] Thermal conductivity enhancer: 1.0~2.0wt%;

[0049] Polymer support material: 17~27wt%.

[0050] The multi-crosslinked network aerogel is composed of the following components by mass percentage:

[0051] Gelatin: 50%~70wt%;

[0052] Sodium alginate: 29~49wt%;

[0053] Cross-linking agent boric acid: 0.5~3wt%;

[0054] Cross-linking agent glutaraldehyde: 0.5~3wt%.

[0055] Preferably, the inorganic solid-liquid phase change material is one to three of sodium acetate trihydrate, barium hydroxide octahydrate, calcium sulfate dihydrate, potassium aluminum sulfate dodecahydrate, ammonium aluminum sulfate dodecahydrate, magnesium chloride hexahydrate, magnesium sulfate heptahydrate, calcium nitrate tetrahydrate, zinc chloride hexahydrate and sodium thiosulfate pentahydrate.

[0056] Preferably, the thermal conductivity enhancer is one to three of expanded graphite, carbon nanotubes, carboxylated carbon nanotubes, graphene, graphene oxide, titanium dioxide, aluminum oxide, zinc oxide, sodium chloride, nanosilver, nanocopper, and nanogold.

[0057] Preferably, the main polymer support material is 1 to 3 of SIS, SBS, SEBS, SEPS, and TPEE.

[0058] Example 1

[0059] (1) Mix 1.0 g of gelatin (Ge) and 0.4 g of sodium alginate (SA), stir, heat and dissolve in acetic acid solution. Then, add 0.01 g of boric acid, stir for 2 h, and then add 200 μL of glutaraldehyde solution. After stirring together for 0.5 h, put the resulting solution into a mold, then freeze it in a -20°C refrigerator for 12 h, and finally freeze-dry it in a freeze dryer for 24 h to obtain Ge / SA aerogel;

[0060] (2) At 50°C, 4.6g of TPEE was dissolved in a dichloromethane solution. After half an hour, TPEE was evenly dissolved. Secondly, 19.3g of SAT was heated to a liquid state at 50°C, and 2.8g of EG was added thereto for adsorption. The adsorbed powder was then crushed using a ball mill, and then placed into a TPEE solution for mixing, and adsorbed in a vacuum drying oven at 50°C for two hours. Subsequently, the mixture was placed in the air to cause the solvent dichloromethane to volatilize. Finally, the sample was placed in a vacuum drying oven for 24 hours to remove the residual dichloromethane solvent and obtain the STE material;

[0061] (3) Coat the adhesive on the surface of the STE material, then place the aerogel on its surface and cure it at room temperature for 48 h.

[0062] In order to evaluate the thermal protection effect of the prepared coupling material, an actual simulated thermal insulation test was performed on it. A ceramic heating plate (35*21*5 mm) was used to simulate a high temperature environment to evaluate the thermal insulation performance of the composite material. First, the material to be evaluated was placed on the ceramic heating plate, and the two were fixed with a mold, and then the thermocouples were placed on both sides of the sample to be tested. Subsequently, a DC regulated power supply (IT6722A, China Itech Electronics Co., Ltd.) was used to power and heat the ceramic heating plate, and a temperature recorder (MIK-R5000C, Hangzhou Meikong Automation Technology Co., Ltd., China) was used to record the temperature difference on both sides of the sample to evaluate the thermal insulation performance of the sample.

[0063] Example 2

[0064] The STE material is composed of: inorganic solid-liquid phase change material SAT: 72wt%; polymer support material TPEE: 27wt%; thermal conductivity enhancer EG: 1%. Other conditions are the same as those in Example 1.

[0065] Example 3

[0066] The STE material is composed of: inorganic solid-liquid phase change material SAT: 74wt%; polymer support material TPEE: 25wt%; thermal conductivity enhancer EG: 1%. Other conditions are the same as those in Example 1.

[0067] Example 4

[0068] The STE material is composed of: inorganic solid-liquid phase change material SAT: 76wt%; polymer support material TPEE: 23wt%; thermal conductivity enhancer EG: 1%. Other conditions are the same as those in Example 1.

[0069] Example 5

[0070] In the STE material, the following components are added: inorganic solid-liquid phase change material SAT: 78wt%; polymer support material TPEE: 21wt%; thermal conductivity enhancer EG: 1%. Other conditions are the same as those in Example 1.

[0071] Example 6

[0072] In the STE material, the following: inorganic solid-liquid phase change material SAT: 80wt%; polymer support material TPEE: 19wt%; thermal conductivity enhancer EG: 1%. Other conditions are the same as those in Example 1.

[0073] Example 7

[0074] From the infrared spectrum of the material ( Figure 1 In a), it can be seen that for unmodified gelatin, 3296 cm -1 The 1629 cm-1 band belongs to the amide A band, which is the vibration absorption of -NH and -OH in gelatin. -1 The amide I band of gelatin is a characteristic band of stretching vibration of C=O and Schiff base (C=N). The amide II band is at 1540 cm -1 The amide III band is at 1235 cm -1 Nearby, it belongs to the CN stretching vibration and NH bending vibration of gelatin. After adding glutaraldehyde cross-linking and sodium alginate, the group changes are mainly reflected in the changes in the absorption peaks of amino and aldehyde groups. In the GE / SA spectrum after cross-linking, the absorption peaks of amide I band, amide II band and amide III band are located at 1628 cm -1 , 1537 cm -1 and 1238 cm -1 The positions of the characteristic absorption peaks shifted and the intensity of the absorption peaks decreased. This indicates that the aldehyde groups in glutaraldehyde and the amino groups in gelatin undergo cross-linking reactions to form Schiff bases. In addition, the absorption peaks of amide A band, amide II band, and amide III band all shifted, proving that hydrogen bonding forces were formed in gelatin molecules. For SA, 3260 cm -1 The broad characteristic peak at 1594 cm -1 and 1408 cm -1 The characteristic absorption peaks at 1029 cm-1 are attributed to the -COO and CO stretching vibrations of SA. -1 The absorption peak at belongs to the COC group. After adding boric acid and gelatin, the absorption peaks of -OH and -COO change significantly. Figure 1As can be seen in a, in the spectrum of cross-linked GE / SA, the absorption peak of -OH shifts to 3286 cm -1 The absorption peaks of -COO and CO shifted to 1627 cm -1 and 1405 cm -1 This indicates that the boric acid and SA are cross-linked through hydrogen bonding.

[0075] Characterization of materials by nitrogen physical adsorption and mercury intrusion method ( Figure 1 It can be seen from (bc) that the pore size distribution curves of the three aerogels are mainly distributed between 20 and 200 μm, which indicates that the three composite aerogels are mainly composed of macropores.

[0076] From the compressive strength of the material ( Figure 2 As can be seen in Figure a), the compressive strength of Ge / SA composite aerogels is higher than that of Ge and SA composite aerogels. This is attributed to the multiple cross-linked networks formed between them, which significantly enhances the mechanical properties of Ge / SA composite aerogel materials.

[0077] From the infrared spectrum of the material ( Figure 2 As can be seen in b), the limiting oxygen index of Ge aerogel is only 20.6%, which is a flammable material; while the limiting oxygen index of SA aerogel and Ge / SA composite aerogel are 27.1% and 35.2%, respectively, which are flame retardant materials. This is mainly due to the cross-linking network formed between SA and boric acid, which provides the Ge / SA composite aerogel with good flame retardant properties.

[0078] Figure 2 Figure c is the thermal insulation effect diagram of Ge / SA composite aerogel. When the thickness is reduced to 5 mm, the temperature difference before and after is also 107 °C, indicating that it has very good thermal insulation performance.

[0079] Figure 3 The shape effect diagram of SAT and STE. It can be seen that after heating for 30 min, SAT has leaked, while SAT / TPEE / EG still maintains a stable shape without leakage.

[0080] Figure 4 The following are photos of STE bending at different temperatures. It can be seen from the figure that CPCM cannot bend at 20°C and bends slightly at 30°C. However, CPCM can be well bent and twisted in the temperature range of 40-50°C, which will help to fit more closely with the aerogel and improve the thermal protection efficiency.

[0081] Figure 5Figure a is the DSC spectra of SAT, SAT / TPEE and SAT / TPEE / EG in Example 1; it can be seen that SAT / TPEE / EG has two peaks, approximately in the range of 50-75°C and 75-150°C, corresponding to latent heat storage and thermochemical heat storage, respectively, and these two stages correspond to SAT losing one crystal water and two crystal waters, respectively. The phase change enthalpy of CPCM is calculated to be 211.5 J / g, the thermochemical decomposition enthalpy is 600.4 J / g, and the total heat storage density is 811.9 J / g.

[0082] from Figure 5 b is the limiting oxygen index of SAT / TPEE and SAT / TPEE / EG. It can be seen that the limiting oxygen index of both is relatively high, and both are flame retardant materials, indicating that both have excellent flame retardancy.

[0083] Figure 5 Figure c shows the thermal insulation performance of the heating plate and SAT / TPEE / EG at different thicknesses. From the results, we can see that as the thickness increases, the thermal insulation gradually increases. Considering that the thermal protection material should not be too thick, we finally chose 5 mm as the optimal thickness.

[0084] Figure 6 In the figure, a is the thermal insulation performance of the heating plate and the GTE-SAT / TPEE / EG coupling material, and b is the thermal insulation performance of the Ge / SA composite aerogel and the SAT / TPEE / EG material alone. From the results, it can be seen that the thermal insulation performance of the Ge / SA composite aerogel is better when it is close to the heat source, and the temperature can be controlled below 90 °C. In addition, we also measured the thermal insulation performance of STE and Ge / SA aerogels of the same thickness. It can be found that the final upper temperature of STE is about 182 °C, while the final upper temperature of GE / SA is 111 °C, which is not as good as the thermal insulation performance of the coupling of the two at the same thickness, which proves the superiority of our coupling material.

[0085] The preparation method of the phase change material also includes: sodium acetate trihydrate, barium hydroxide octahydrate, calcium sulfate dihydrate, potassium aluminum sulfate dodecahydrate, ammonium aluminum sulfate dodecahydrate, magnesium chloride hexahydrate, magnesium sulfate heptahydrate, calcium nitrate tetrahydrate, zinc chloride hexahydrate and sodium thiosulfate pentahydrate

[0086] Embodiment 8-13

[0087] Barium hydroxide octahydrate was used instead of sodium acetate trihydrate as the phase change material to obtain the corresponding thermo-flexible composite phase change material, and other conditions were consistent with those of Example 1-6.

[0088] Examples 14-19

[0089] Calcium sulfate dihydrate was used instead of sodium acetate trihydrate as the phase change material to obtain the corresponding thermo-flexible composite phase change material, and other conditions were consistent with those of Example 1-6.

[0090] Examples 20-25

[0091] Potassium aluminum sulfate dodecahydrate was used instead of sodium acetate trihydrate as the phase change material to obtain the corresponding thermo-flexible composite phase change material, and other conditions were consistent with those of Example 1-6.

[0092] Examples 26-31

[0093] Ammonium aluminum sulfate dodecahydrate was used instead of sodium acetate trihydrate as the phase change material to obtain the corresponding thermo-flexible composite phase change material. Other conditions were the same as those in Example 1-6.

[0094] Examples 32-37

[0095] Magnesium chloride hexahydrate is used instead of sodium acetate trihydrate as the phase change material to obtain the corresponding thermo-flexible composite phase change material, and other conditions are consistent with those of Example 1-6.

[0096] Examples 38-43

[0097] Magnesium sulfate heptahydrate was used instead of sodium acetate trihydrate as the phase change material to obtain the corresponding thermo-flexible composite phase change material. Other conditions were the same as those in Example 1-6.

[0098] Examples 44-49

[0099] Calcium nitrate tetrahydrate was used instead of sodium acetate trihydrate as the phase change material to obtain the corresponding thermo-flexible composite phase change material, and other conditions were consistent with those of Example 1-6.

[0100] Examples 50-55

[0101] Zinc chloride hexahydrate is used instead of sodium acetate trihydrate as the phase change material to obtain the corresponding thermo-flexible composite phase change material, and other conditions are consistent with those of Example 1-6.

[0102] Examples 56-61

[0103] Sodium thiosulfate alcohol pentahydrate was used instead of sodium acetate trihydrate as the phase change material to obtain the corresponding thermo-flexible composite phase change material, and other conditions were consistent with those of Example 1-6.

[0104] Examples 62-67

[0105] The corresponding thermo-flexible composite phase change material was obtained by using SIS instead of TPEE as the polymer support material, and other conditions were consistent with those of Examples 1-6.

[0106] Examples 68-73

[0107] The corresponding thermo-flexible composite phase change material was obtained by using SBS instead of TPEE as the polymer support material, and other conditions were consistent with those of Example 1-6.

[0108] Examples 74-79

[0109] SEBS was used instead of TPEE as the polymer support material to obtain the corresponding thermo-flexible composite phase change material, and other conditions were consistent with those of Example 1-6.

[0110] Examples 80-85

[0111] The corresponding thermo-flexible composite phase change material was obtained by using SEPS instead of TPEE as the polymer support material, and other conditions were consistent with those of Examples 1-6.

[0112] Examples 86-91

[0113] The corresponding thermo-flexible composite phase change material was obtained by using carbon nanotubes instead of expanded graphite as a thermal conductive additive, and other conditions were consistent with those of Examples 1-6.

[0114] Examples 92-97

[0115] The corresponding thermo-flexible composite phase change material was obtained by using carboxylated carbon nanotubes instead of expanded graphite as a thermal conductive additive, and other conditions were consistent with those of Examples 1-6.

[0116] Examples 98-103

[0117] Graphene is used instead of expanded graphite as a thermal conductive additive to obtain the corresponding thermally induced flexible composite phase change material, and other conditions are consistent with those of Examples 1-6.

[0118] Examples 104-109

[0119] Graphene oxide is used instead of expanded graphite as a thermal conductive additive to obtain a corresponding thermally induced flexible composite phase change material, and other conditions are consistent with those of Examples 1-6.

[0120] Examples 110-115

[0121] The corresponding thermo-flexible composite phase change material was obtained by using carbon nanotubes instead of expanded graphite as a thermal conductive additive, and other conditions were consistent with those of Examples 1-6.

[0122] Examples 116-121

[0123] Titanium dioxide is used as a thermal conductive additive instead of expanded graphite to obtain a corresponding thermally induced flexible composite phase change material, and other conditions are consistent with those of Examples 1-6.

[0124] Examples 122-127

[0125] Alumina was used as a thermal conductive additive instead of expanded graphite to obtain the corresponding thermally induced flexible composite phase change material, and other conditions were consistent with those of Example 1-6.

[0126] Examples 128-133

[0127] The corresponding thermo-flexible composite phase change material was obtained by using zinc oxide instead of expanded graphite as a thermal conductive additive, and other conditions were consistent with those of Examples 1-6.

[0128] Examples 134-139

[0129] The corresponding thermo-flexible composite phase change material was obtained by using nano-silver instead of expanded graphite as a thermal conductive additive, and other conditions were consistent with those of Examples 1-6.

[0130] Examples 140-145

[0131] The corresponding thermo-flexible composite phase change material was obtained by using nano copper instead of expanded graphite as a thermal conductive additive, and other conditions were consistent with those of Examples 1-6.

[0132] Examples 146-151

[0133] The corresponding thermo-flexible composite phase change material was obtained by using nano-gold instead of expanded graphite as a thermal conductive additive, and other conditions were consistent with those of Example 1-6.

[0134] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. Thermo-flexible composite phase change material coupled with multi-cross-linked network aerogel material, characterized by: The mass percentage of each component in the coupling material is: Multi-crosslinked network aerogel: 0.5~1.5wt%; Thermally induced flexible composite phase change material: 96.5~97.5wt%; Binder: 1~3wt%; Adhesives are used to bond the multi-crosslinked network aerogel and the thermo-induced flexible composite phase change material together; The mass percentage of each component in the multi-crosslinked network aerogel material is: Gelatin: 50%~70wt%; Sodium alginate: 29~49wt%; Cross-linking agent boric acid: 0.5~3wt%; Cross-linking agent glutaraldehyde: 0.5~3wt%; The multi-crosslinked network aerogel adopts a double crosslinking agent to crosslink with gelatin and sodium alginate to form a stable multi-network structure; The mass percentage of each component in the thermoflexible composite phase change material is: Inorganic solid-liquid phase change material: 72~82wt%; Thermal conductivity enhancer: 1.0~2.0wt%; Polymer support material: 17~27wt%.

2. The thermo-flexible composite phase change material coupled with a multi-crosslinked network aerogel material according to claim 1, characterized in that: The inorganic solid-liquid phase change material is one to three of sodium acetate trihydrate, calcium sulfate dihydrate, potassium aluminum sulfate dodecahydrate, ammonium aluminum sulfate dodecahydrate, magnesium chloride hexahydrate, magnesium sulfate heptahydrate, calcium nitrate tetrahydrate, zinc chloride hexahydrate and sodium thiosulfate pentahydrate.

3. The thermo-flexible composite phase change material coupled with a multi-crosslinked network aerogel material according to claim 1, characterized in that: The thermal conductivity enhancer is one to three of expanded graphite, carbon nanotubes, carboxylated carbon nanotubes, graphene, graphene oxide, titanium dioxide, aluminum oxide, zinc oxide, sodium chloride, nanosilver, nanocopper, and nanogold.

4. The thermo-flexible composite phase change material and multi-crosslinked network aerogel coupling material according to claim 1, characterized in that: The polymer support material is one to three of styrene-isoprene-styrene block copolymer, styrene-butadiene-styrene block copolymer, styrene-ethylene-butylene-styrene block copolymer, hydrogenated styrene-isoprene-styrene block copolymer, and thermoplastic polyester elastomer.

5. The method for preparing the thermo-flexible composite phase change material coupled with a multi-crosslinked network aerogel material according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Mix gelatin and sodium alginate, stir, heat and dissolve in acetic acid solution; Then, boric acid was added thereto, and after stirring, glutaraldehyde solution was added; After being stirred together, the obtained solution is placed in a mold, then frozen, and finally freeze-dried in a freeze dryer to obtain Ge / SA aerogel; (2) dissolving the polymer support material in a solvent until it is uniformly dissolved; Secondly, the inorganic solid-liquid phase change material is heated to a liquid state, and a thermal conductivity enhancer is added thereto for adsorption, and then the material is crushed by a ball mill, and then added to a polymer support material solution for mixing and adsorption; the solvent is removed to obtain a thermally induced flexible composite phase change material; (3) The adhesive is coated on the surface of the thermoflexible composite phase change material, and then the Ge / SA aerogel is placed on the surface of the thermoflexible composite phase change material and cured at room temperature to obtain a thermoflexible composite phase change material and a multi-crosslinked network aerogel coupling material.

6. The method for preparing the thermo-flexible composite phase change material and multi-crosslinked network aerogel coupling material according to claim 5, characterized in that: The solvent is one to three of tetrahydrofuran, dioxane, petroleum ether, acetone, butanone, chloroform, dichloromethane, carbon tetrachloride, carbon disulfide, dimethylformamide, dimethyl sulfoxide, benzene, toluene, xylene, nitrobenzene, chlorobenzene, cyclohexane or n-hexane.

7. The use of the thermo-flexible composite phase change material and the multi-crosslinked network aerogel coupling material according to any one of claims 1 to 4, characterized in that: The material is used in the field of thermal protection of buildings, batteries and electronic devices.

Citation Information

Patent Citations

  • Aerogel-based phase-change composite material for thermal management of electronic components and preparation method and application of aerogel-based phase-change composite material

    CN114874755A

  • High-strength photo-thermal response surface lubrication hydrogel and preparation method thereof

    CN114933716A

  • High-thermal-conductivity flexible composite phase change material as well as preparation method and application thereof

    CN116622342A

  • Double-network interpenetrating heat release controllable shape-stabilized phase change material and preparation and application thereof

    CN118185578A

  • Plastic composite shape-stabilized phase change material as well as preparation method and application thereof

    CN118421270A

Cited By

  • Flexible functional composite material with excellent thermal management capability and preparation method thereof

    CN121108745A

  • A flexible functional composite material with excellent thermal management capabilities and its preparation method

    CN121108745B